2016
DOI: 10.1021/acsami.6b04011
|View full text |Cite
|
Sign up to set email alerts
|

Shape- and Interface-Induced Control of Spin Dynamics of Two-Dimensional Bicomponent Magnonic Crystals

Abstract: Controlled fabrication of periodically arranged embedded nanostructures with strong interelement interaction through the interface between the two different materials has great potential applications in spintronics, spin logic, and other spin-based communication devices. Here, we report the fabrication of two-dimensional bicomponent magnonic crystals in form of embedded Ni80Fe20 nanostructures in Co50Fe50 thin films by nanolithography. The spin wave (SW) spectra studied by a broadband ferromagnetic resonance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…The exciting new frontier of spintronics [1] and magnonics [2,3] research is driven by the need of utilizing spin-orbit (SO) effect for obtaining pure spin current [4]. An important aspect of improving the performance of the device is to minimize Joule heating, which requires fundamentally pure spin current [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The exciting new frontier of spintronics [1] and magnonics [2,3] research is driven by the need of utilizing spin-orbit (SO) effect for obtaining pure spin current [4]. An important aspect of improving the performance of the device is to minimize Joule heating, which requires fundamentally pure spin current [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies on the dynamic susceptibility of antidot arrays have shown that by modifying the hole density or hole geometry, it is possible to achieve a reasonable degree of control over the number of resonant peaks, their amplitude and their position 53 , 54 . In fact, it has been reported that antidot arrays with holes of different shape and size substantially modify the spin wave spectra of these systems 55 57 , establishing the geometrical variation of the antidots as the key for the tunability of spin wave structures. Furthermore, not only the shape and density of the antidot arrays play an important role in the dynamic properties of these structures, but also the lattice ordering and its symmetry have proven to be a feasible way to control and modulate the spin wave spectra 57 59 .…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental realization of bi-component MCs [21][22][23] , the interfaces between layers can suffer from oxidation, and so, a significant change of magnetic properties near the edges can be expected. This is especially important in the case of ferromagnetic metals because of arXiv:1905.11016v2 [cond-mat.mes-hall] 17 Jul 2019 their high reactivity with oxygen, 24 giving rise to oxides displaying paramagnetic or antiferromagnetic properties at temperatures above and below the Neel temperature, respectively.…”
Section: Introductionmentioning
confidence: 99%